Parthenogenetic activation of buffalo (Bubalus bubalis) oocytes: comparison of different activation reagents and different media on their developmental competence and quantitative expression of developmentally regulated genes. Issue 1 (2nd February 2021) - Singh, K.P.; Mohapatra, S.K.; Kaushik, R.; Singh, M.K.; Palta, P.; Singla, S.K.; Manik, R.S.; Chauhan, M.S.
Summary: This study was carried out to compare the efficacy of different methods to activate buffalo A + B and C + D quality oocytes parthenogenetically and to study the in vitro developmental competence of oocytes and expression of some important genes at the different developmental stages of parthenotes. The percentage of A + B oocytes (62.16 ± 5.06%, range 53.8–71.3%) was significantly higher ( P < 0.001) compared with that of C + D oocytes (37.8 ± 5.00%, range 28.6–46.1%) retrieved from slaughterhouse buffalo ovaries. Among all combinations, ethanol activation followed by culture in research vitro cleave medium gave the highest cleavage and blastocyst yields for both A + B and C + D grade oocytes. Total cell numbers, inner cell mass/trophectoderm ratio and apoptotic index of A + B group blastocysts were significantly different ( P < 0.05) from their C + D counterpart. To determine the status of expression patterns of developmentally regulated genes, the expression of cumulus–oocyte complexes, fertilization, developmental competence and apoptotic-related genes were also studied in parthenogenetically produced buffalo embryos at different stages, and indicated that the differential expression patterns of the above genes had a role in early embryonic development.